The complexities of communication at hospital discharge of older patients: a qualitative study of healthcare professionals' views - Henrik Cam; Björn Wennlöf; Ulrika Gillespie; Kristin Franzon; Elisabet I. Nielsen; Mia Ling; Karl-Johan Lindner; Thomas Gerardus Hendrik Kempen; Sofia Kälvemark Sporrong (BMC, 2023)
Abstract Background Hospital discharge of older patients is a high-risk situation in terms of patient safety. Due to the fragmentation of the healthcare system, communication and coordination between stakeholders are required at discharge. The aim of this study was to explore communication in general and medication information transfer in particular at hospital discharge of older patients from the perspective of healthcare professionals (HCPs) across different organisations within the healthcare system. Methods We conducted a qualitative study using focus group and individual or group interviews with HCPs (physicians, nurses and pharmacists) across different healthcare organisations in Sweden. Data were collected from September to October 2021. A semi-structured interview guide including questions on current medication communication practices, possible improvements and feedback on suggestions for alternative processes was used. The data were analysed thematically, guided by the systematic text condensation method. Results In total, four focus group and three semi-structured interviews were conducted with 23 HCPs. Three main themes were identified: 1) Support systems that help and hinder describes the use of support systems in the discharge process to compensate for the fragmentation of the healthcare system and the impact of these systems on HCPs' communication; 2) Communication between two separate worlds depicts the difficulties in communication experienced by HCPs in different healthcare organisations and how they cope with them; and 3) The large number of medically complex patients disrupts the communication reveals how the highly pressurised healthcare system impacts on HCPs' communication at hospital discharge. Conclusions Communication at hospital discharge is hindered by the fragmented, highly pressurised healthcare system. HCPs are at risk of moral distress when coping with communication difficulties. Improved communication methods at hospital discharge are needed for the benefit of both patients and HCPs.